Nyonya cuisine as culinary capital : a feminist study of food and women's empowerment in english-language fiction by Malaysian chinese women writers - Siti Zaharah Shahiera Fauzi (Kulliyyah of Islamic Revealed Knowledge and Social Sciences, 2020)
Food, in many cultures around the world, is a key essential in sustaining and preserving the notion of identity, home and culture. In literary writing, food preparation and consumption feature significantly in the discussions on gender and power. Gendered discourses around food have heavily concentrated on women as their prescribed responsibility as nurturers in the community entails that they have a special relationship with food; often, a troubled one. Over the years scholars have portrayed women as resistant to or oppressed by food. However, the course of this relationship becomes irrelevant when food and foodways are reframed as positive experiences in the lives of women, as they establish their independence and agency. In the Malaysian literary scene, Selina Siak Chin Yoke and Chan Ling Yap are some of the women writers who have captured the changing nature of women's relationships with food. Their novels, The Woman Who Breathed Two Worlds (2016) and Sweet Offerings (2009), respectively, encapsulate the myriad layers to the relationship women have with food. More importantly, the representation of Peranakan Chinese women in their works as well as the characters' relationship with food and foodwork will become the premise of this study. The work of these writers would provide adequate evidence on the discussion on women's identity, power and status vis-à-vis food. It is hoped that this study would contribute to the discourse of food and women's empowerment in fiction in the English language.